Characteristics of Local Wisdom in Building Character Based on the Perspectives of Teachers and Students in Batu City Elementary Schools - Sofiyah, Raden Ajeng; Suwandayani, Beti Istanti; Kumalasani, Maharani Putri (Jayapangus Press, 2025)
This study aims to examine teachers' and students' perspectives on the role of local wisdom in building student character in elementary schools. Using a descriptive method with a qualitative approach, data was collected through in-depth interviews and observations in several elementary schools. Regional Pride by developing a sense of pride in the cultural richness and uniqueness of the Batu region through school projects. This research adopts a descriptive method with a qualitative approach. Data collection involves observation, interviews with teachers and students, and documentation, allowing for direct observation of classroom dynamics and gathering insights from participants. The research follows Miles and Huberman's three streams of activities, beginning with data collection from various sources. The results showed that teachers see local wisdom as an important source of value in character education, as it can strengthen cultural identity and instill positive values among students. Students also recognized the benefits of engaging in local wisdom-based activities, which made students appreciate their own culture more. However, challenges faced include teachers' lack of knowledge about local wisdom and limited resources to integrate it into the curriculum. This study recommends the need for training for teachers and closer collaboration between schools and communities to overcome these obstacles. With the right approach, local wisdom can be effectively integrated in learning, contributing to better character development of students and strengthening their love for local culture.